2014
DOI: 10.1039/c3cp55214d
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen vacancy formation and annihilation in lanthanum cerium oxide as a metal reactive oxide on 4H-silicon carbide

Abstract: A mechanism regarding the redox reaction in lanthanum cerium oxide (LaxCeyOz) post-deposition annealed in reducing and oxidizing atmosphere was schematized and discussed in association with the presence of lanthanum as a substitutional cation. Analyses have been performed using X-ray diffraction, energy-filtered transmission electron microscopy, scanning transmission electron microscope-energy dispersive spectroscopy line scan, and capacitance-voltage measurements. The results showed the presence of an oxygen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…. The acquisition of a larger c (0.5212–0.5220 nm) than the GaN (0.5185 nm) signified the occurrence of lattice expansion in the nonporous film . In comparison, larger c values were obtained by the films etched in 1:1 and 1:2 solution while the films etched in 1:3 and 1:4 solution showed smaller c values than the nonporous film (inset of Fig.…”
Section: Resultsmentioning
confidence: 92%
“…. The acquisition of a larger c (0.5212–0.5220 nm) than the GaN (0.5185 nm) signified the occurrence of lattice expansion in the nonporous film . In comparison, larger c values were obtained by the films etched in 1:1 and 1:2 solution while the films etched in 1:3 and 1:4 solution showed smaller c values than the nonporous film (inset of Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Beside the above approaches, introducing oxygen vacancies (OVs) is a relatively simple and economic alternative for developing high-performing electrocatalysts. [28][29][30] Depending on the sample treatment, thermal heating or radiation, OVs can be created in the bulk of and at the surface of metal oxides. [31][32][33][34][35] Kong 34 and Yan 35 et al reported that tuning the relative concentration ratio of bulk OVs to surface OVs in TiO 2 can enhance the photocatalytic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Since, bivalent doped ceria materials are thermally unstable, and phase segregation occurs which makes the oxygen migration more difficult. This consideration has shrunk down to select trivalent cations as dopants in the aliovalent section to improve the ceria catalytic properties [26].…”
Section: Introductionmentioning
confidence: 99%